The incidence of different cystic fibrosis mutations in the Scottish population: effects on prenatal diagnosis and genetic counselling. - Shrimpton, A E (1991)
We present an analysis of the frequency of 16 different cystic fibrosis (CF) mutant alleles in the Scottish population. Each allele was detected in DNA amplified by the polymerase chain reaction (PCR) either directly on polyacrylamide gels, on agarose gels after restriction enzyme digestion, or by using allele specific oligonucleotides. Among 506 CF chromosomes, of predominantly Scottish origin, the frequencies of the different mutations were delta F508 0.71, G551D 0.05, G542X 0.04, R117H 0.01, 1717-1G----A 0.01, A455E + delta I507 + R553X + R560T + W1282X + 621 + 1G----T combined 0.03, unpublished 0.01, and unknown 0.13. No examples of D110H, R347P, S549N, S549I, or 2566ins AT mutations were found. The relevance of this type of analysis for both prenatal diagnosis and heterozygote screening is discussed.